Analysis of Classroom Verbal Interaction Using Fiacs (Flanders Interaction Analysis Categories System) - Faiqotur Rizkiyah; Umi Salamah (Darussalam English Journal (DEJ), 2023)
One of the primary factors that influence the teaching and learning process is interaction. Verbal interaction is the most interaction happened between teacher and students in the classroom. The quality of verbal interaction affect the result of teaching and learning itself. Thus, this study aimed to find out teacher-students talk characteristic during classroom interaction using FIACS and to find out the dominant talk between teacher and students in classroom interaction. This study was qualitative research. To achieve the purposes of this study the writer used observation which was adopted by Flander’s Interaction Analysis Category to find out verbal interaction between teacher and student. The researcher also use interview and recording for get the data. The study found that all teachers used all FIAC categories and the dominance talk was the teacher’s talk. The teacher speaks about 77 per cent in the classroom while students 13 per cent. From the result, it is suggested that teacher should give more opportunities to the students to speak and interact during tteaching and learning process